Optimization of performance carbon-based nanolubricant on Ti6Al4V Pin on disc testing using taguchi method - Puspitasari, Poppy; Pramono, Diki Dwi; Putra, Chandra Setiawan; Permanasari, Avita Ayu; Hidayat Syah Lubis, Abdul Munir; Abdullah, Muhammad Ilman Hakimi Chua (2023)
Pin-on-disc (PoD) testing extensively to investigate material sliding behavior and relevant wear mechanisms under different tribological conditions, result of Pin on Disc testing is worn and coefficient of friction. To identify the optimal parameters of the Pin on Disc test can use the taguchi optimization method. Taguchi method is a reliable and cost-effective approach to optimization, especially when several factors may affect performance. Taguchi was chosen as the optimization method due to its reliability and the fact that it requires fewer experiments compared to other methods such as full factorial design. From the result optimization using Taguchi methods shows the best parameters for pin-on-disc testing using Taguchi. To reduce wear rate and friction coefficient by optimizing control parameters for pin-on-disc testing of material dry sliding wear behavior. Based on the S/N ratio of COF, it is known that the large load parameter has the highest influence on COF because it produces the highest delta value compared to other variables. This also shows that the optimal combination is to get the best COF value in the pin on disc test is oil type SWCNT, load 20N, and Speed 150 RPM. Based on the results of the response S/N ratio of wear, it is known that the large load parameter has the highest influence on wear because it produces the highest delta value compared to other variables. This also shows that the optimal combination is to get the best COF value in the pin on disc test is oil type SWCNT, load 20N, and Speed 120 RPM. The combination of SWCNT oil type, load 20 N and speed 120 RPM is the optimal parameter combination for COF and wear values. The results of ANOVA show that percentage load has the highest contribution of about 61.83%, and the other parameters have lower contributions.